Early variations in white matter microstructure and depression outcome in adolescents with subthreshold-depression - Vulser, Hélène; Martinot, Marie-Laure Paillère; Artiges, Eric; Miranda, Ruben; Pentilla, Jani; Grimmer, Yvonne; van Noort, Betteke M.; Stringaris, Argyris; Struve, Maren; Fadai, Tahmine; Kappel, Viola; Goodman, Robert; et al. (American Psychiatric Publishing, 2018)
Objective: White matter microstructure alterations have recently been associated with adolescence depressive episodes, but it is unknown whether they predate depression. We investigated whether subthreshold-depression in adolescence is associated with white matter microstructure variations and whether they relate to depression outcome. Method: Adolescents with subthreshold-depression (n=96) and healthy controls (n=336), drawn from a community-based cohort, were compared using diffusion tensor imaging and whole-brain tractbased spatial statistics (TBSS) at age 14 to assess white matter microstructure. They were followedup at age 16 to assess depression. Probabilistic tractography was used to reconstruct white matter streamlines from the TBSS analysis resulting regions, and along bundles implicated in emotion regulation, the uncinate fasciculus and the cingulum. We searched for mediating effects of white matter microstructure on the relationship between baseline subthreshold-depression and depression at follow-up, and then explored the specificity of the findings. Results: Lower fractional anisotropy (FA) and higher radial diffusivity were found in the anterior corpus callosum in the adolescents with subthreshold-depression. Tractography analysis showed that they also had lower FA in the right cingulum streamlines, along with lower FA and higher mean diffusivity in tracts connecting the corpus callosum to the anterior cingulate cortex. The relation between baseline subthreshold-depression and follow-up depression was mediated by FA values in the latter tracts, and lower FA values in those tracts distinctively predicted higher individual risk for depression. Conclusions: Early FA variations in tracts projecting from the corpus callosum to the anterior cingulate cortex might denote higher risk of transition to depression in adolescents.